A case study of autonomy and motivation in a student-led game development project. Issue 2 (2nd July 2016) - Prigmore, M.; Taylor, R.; De Luca, D.
Abstract: This paper presents the findings of an exploratory case study into the relationship between student autonomy and motivation in project based learning, using Self-Determination Theory (SDT) to frame the investigation. The case study explores how different forms of motivation affect the students' response to challenges and their intention to complete the project. Earlier studies have made little explicit use of theoretical perspectives on student autonomy and motivation, a weakness this study attempts to address. As an exploratory case study seeking to evaluate the suitability of a particular theoretical framework, we chose a small case: three students on a one-term computer games development project. Given the small scale, the approach is necessarily qualitative, drawing on project documentation and one-to-one interviews with the students. Our conclusion is that the concepts of SDT provide a useful framework for analysing students' motivations to undertake project work, and its predictions can offer useful guidance on how to initiate and supervise such projects.